Genome-Wide Association Study of Antiphospholipid Antibodies. (24th February 2013) - Kamboh, M. Ilyas; Wang, Xingbin; Kao, Amy H.; Barmada, Michael M.; Clarke, Ann; Ramsey-Goldman, Rosalind; Manzi, Susan; Demirci, F. Yesim
Abstract : Background . The persistent presence of antiphospholipid antibodies (APA) may lead to the development of primary or secondary antiphospholipid syndrome. Although the genetic basis of APA has been suggested, the identity of the underlying genes is largely unknown. In this study, we have performed a genome-wide association study (GWAS) in an effort to identify susceptibility loci/genes for three main APA: anticardiolipin antibodies (ACL), lupus anticoagulant (LAC), and anti- β 2 glycoprotein I antibodies (anti- β 2 GPI). Methods . DNA samples were genotyped using the Affymetrix 6.0 array containing 906, 600 single-nucleotide polymorphisms (SNPs). Association of SNPs with the antibody status (positive/negative) was tested using logistic regression under the additive model. Results . We have identified a number of suggestive novel loci withP < E - 05 . Although they do not meet the conservative threshold of genome-wide significance, many of the suggestive loci are potential candidates for the production of APA. We have replicated the previously reported associations of HLA genes and APOH with APA but these were not the top loci. Conclusions . We have identified a number of suggestive novel loci for APA that will stimulate follow-up studies in independent and larger samples to replicate our findings.